Sebaziöses Carcinoma in situ der extraokulären Haut : Fallbericht und Diskussion eines neuen Entitätskonzepts - Hrudka, Jan; Bezvodová, Alžběta; Arenbergerová, Monika; Sticová, Eva; Bandke, Dave (Der Hautarzt; Zeitschrift fur Dermatologie, Venerologie, und verwandte Gebiete, 2020)
Sebaceous carcinoma in situ (SCIS) is a rare intraepidermal neoplasia, mostly occurring on the eyelid and the face. Despite abundant literature on invasive sebaceous carcinoma, there are relatively few articles about SCIS. We report the case of 78-year-old woman suffering from SCIS of the left cheek, presenting as an erythematous skin lesion. The histological examination revealed intraepidermal and intraadnexal population of atypical cells with foamy cytoplasm and with immunohistochemical adipophilin-, cytokeratin-7- and EMA-positivity in the tumor cells.
Keywords: Histology; nádory kůže; Humans; Skin Neoplasms; Adenocarcinoma, Sebaceous; Sebaceous Gland Neoplasms; Perilipin-2; Female; Aged; Carcinoma in Situ; karcinom in situ; senioři; lidé; Skin biopsy; ženské pohlaví; Cryotherapy; perilipin 2; Intraepidermal carcinoma; sebaceózní adenokarcinom; Sebaceous gland neoplasms; nádory mazových žláz